Dissociation Between Hormonal Counterregulatory Responses and Cerebral Glucose Metabolism During Hypoglycemia - Lee, John J. (Diabetes, 2017)
Hypoglycemia is the most common complication of diabetes, causing morbidity and death. Recurrent hypoglycemia alters the cascade of physiological and behavioral responses that maintain euglycemia. The extent to which these responses are normally triggered by decreased whole-brain cerebral glucose metabolism (CMR(glc)) has not been resolved by previous studies. We measured plasma counterregulatory hormonal responses and whole-brain CMR(glc) (along with blood-to-brain glucose transport rates and brain glucose concentrations) with 1-[(11)C]-d-glucose positron emission tomography during hyperinsulinemic glucose clamps at nominal plasma glucose concentrations of 90, 75, 60, and 45 mg/dL (5.0, 4.2, 3.3, and 2.5 mmol/L) in 18 healthy young adults. Clear evidence of hypoglycemic physiological counterregulation was first demonstrated between 75 mg/dL (4.2 mmol/L) and 60 mg/dL (3.3 mmol/L) with increases in both plasma epinephrine (P = 0.01) and glucagon (P = 0.01). In contrast, there was no statistically significant change in CMR(glc) (P = 1.0) between 75 mg/dL (4.2 mmol/L) and 60 mg/dL (3.3 mmol/L), whereas CMR(glc) significantly decreased (P = 0.02) between 60 mg/dL (3.3 mmol/L) and 45 mg/dL (2.5 mmol/L). Therefore, the increased epinephrine and glucagon secretion with declining plasma glucose concentrations is not in response to a decrease in whole-brain CMR(glc).